2018
DOI: 10.1016/j.conb.2018.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of population coding in primary sensory cortex

Abstract: That experience shapes sensory tuning in primary sensory cortex is well understood. But effective neural population codes depend on more than just sensory tuning. Recent population imaging and recording studies have characterized population codes in sensory cortex, and tracked how they change with sensory manipulations and training on perceptual learning tasks. These studies confirm sensory tuning changes, but also reveal other features of plasticity, including sensory gain modulation, restructuring of firing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 43 publications
0
16
1
Order By: Relevance
“…Thus enrichment sharpened the L2/3 PYR cell map and strengthened CW responses at both the microscopic (cellular-resolution) and macroscopic levels, with more subtle changes in the L4 map. These L2/3 map changes could reflect use-dependent strengthening of L4-L2/3 or local recurrent projections (Clem and Barth, 2006; Ko et al, 2013), reorganization of cross-columnar projections (Finnerty et al, 1999), or changes in POm thalamic input (Audette et al, 2018) or top-down input (LeMessurier and Feldman, 2018) to L2/3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus enrichment sharpened the L2/3 PYR cell map and strengthened CW responses at both the microscopic (cellular-resolution) and macroscopic levels, with more subtle changes in the L4 map. These L2/3 map changes could reflect use-dependent strengthening of L4-L2/3 or local recurrent projections (Clem and Barth, 2006; Ko et al, 2013), reorganization of cross-columnar projections (Finnerty et al, 1999), or changes in POm thalamic input (Audette et al, 2018) or top-down input (LeMessurier and Feldman, 2018) to L2/3.…”
Section: Discussionmentioning
confidence: 99%
“…The origins and function of such dispersed maps are unclear. L2/3 maps are also robustly plastic to sensory experience (Buonomano and Merzenich, 1998; Feldman and Brecht, 2005; LeMessurier and Feldman, 2018). Appropriate sensory experience is often required for development of normal map topography (Katz and Shatz, 1996), raising the question of whether dispersed, salt-and-pepper maps are a natural feature of L2/3, or may reflect incomplete activity-dependent development due to impoverished sensory experience in rodent laboratory housing.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that experience-induced reductions in the fraction of active cells can be specific to distinct functional subpopulations: 'transient' cells were reduced with experience, but 'sustained' and 'suppressed by contrast' cells showed no change in the fraction of active cells (Weskelblatt and Niell, 2019). Reduced activity for highly familiar stimuli may serve to more efficiently code for stimuli which are predictable, utilizing a smaller population of cells to represent learned information (LeMessurier and Feldman, 2018). On the other hand, enhanced activity for novel stimuli may be involved in the detection of salient and behaviorally meaningful events by augmenting output to downstream targets and facilitating associative plasticity (Ranganath and Rainer, 2003).…”
Section: Experience Reduces Overall Activity and Sharpens Tuningmentioning
confidence: 99%
“…The inter-stimulus activity of VIP cells during sessions with familiar images in the change detection task may be similarly important for enhancing the responses of subsets of excitatory cells to an expected change stimulus, via disinhibition through SST cells. In contrast, during sessions with novel images, VIP activity is driven by stimulus presentation and could serve to increase the gain of stimulus evoked excitatory responses to facilitate learning of new images via associative plasticity (LeMessurier and Feldman, 2018;Ranganath and Rainer, 2003). Future studies examining the evolution of VIP activity across multiple behavior sessions as novel images become familiar, as well as concurrent recordings of VIP and excitatory cells and other inhibitory classes including SST cells, will be critical to determine the time course and mechanistic nature of these interactions.…”
Section: Experience Alters Temporal Dynamics Of Vip Cellsmentioning
confidence: 99%
See 1 more Smart Citation